Administration of a Recombinant Fusion Protein of IFN-γ and CD154 Inhibited the Infection of Chicks with Salmonella enterica - Jingya Zhang; Guofan Ren; Wei Li; Honglin Xie; Zengqi Yang; Juan Wang; Yefei Zhou; Xinglong Wang (Veterinary Sciences)
The cytokines IFN-γ and CD154 have been well established, and they play pivotal roles in immune protection against Salmonella in mice, but their effects and specific mechanisms in Salmonella-infected chickens are less understood. In this study, we conducted animal experiments to screen the highly immunoprotective chIFN-γ-chCD154 fusion protein compared with single protein chIFN-γ or chCD154 in white Leghorn chickens. The results showed that compared with separate pretreatments with chIFN-γ and chCD154, the fusion protein, chIFN-γ-chCD154, synergistically increased survival of infected chickens, reduced bacterial load in feces and organs, and attenuated pathological damage to the liver and cecum. Pretreatment with chIFN-γ-chCD154 also increased humoral immune responses, expression of the tight junction proteins zo-1, occludin, and claudin-1, and the relative abundance of Enterococcus_cecorum, Lactobacillus_helveticus, and Lactobacillus_agilis, which protect against intestinal inflammation. Compared with single protein pretreatment, chIFN-γ-chCD154 significantly upregulated STAT1, IRF1, and GBP1 in infected chickens while decreasing mRNA expression of TLR4, MyD88, NF-κB, TNF-α, IL-6, and IL-1β. In summary, damage to the cecal epithelial barrier and the inflammation induced by S. typhimurium infection was alleviated by chIFN-γ-chCD154 pretreatment through a mechanism involving the TLR4/MyD88/NF-κB and IFN-γ/STAT/IRF1/GBP1 pathways.